116k views
1 vote
If p(x) = x2 – 1 and q(x) = 5(x-1) which expression is equivalent to (p – q)(x)?

A) 5(x – 1) – x2 – 1

B) (5x – 1) – (x2 – 1)

C) (x2 – 1) – 5(x – 1)

D) (x2 – 1) – 5x – 1

2 Answers

3 votes

Answer:

For the given expression (p-q)(x)

Option C will be correct

Explanation:

Given;

p(x) = x^2-1

q(x)= 5(x-1)

Solution:

=(p-q)(x)

=p(x)-q(x)

putting values of p(x) and q(x)

=(x^2-1)-(5(x-1))

=x^2-1-5(x-1)

User SaguiItay
by
5.4k points
4 votes

Answer:

Option C is correct.

The expression which is equivalent to (p-q)(x) is,
x^2 -1 - 5(x-1)

Explanation:

Given:
p(x) = x^2 -1 and q(x) = 5(x-1)

To find the expression which is equivalent to (p-q)(x):

here p and q both are function assuming;

we can write the expression :

(p-q)(x) = p(x) - q(x) =
x^2 -1 - 5(x-1)

therefore, the expression which is equivalent to (p-q)(x) is;
x^2 -1 - 5(x-1)

User Jika
by
6.4k points